Central nervous system multiple myeloma – potential roles for intrathecal therapy and measurement of cerebrospinal fluid light chains. (29th May 2013) - Lee, Denise; Kalff, Anna; Low, Michael; Gangatharan, Shane; Ho, Prahlad; Bajel, Ashish; Ritchie, David; Grigg, Andrew; Spencer, Andrew
Summary: Central nervous system (CNS) multiple myeloma (MM) is exceedingly rare and portends a dismal prognosis. While immunomodulators have contributed to the improvement in survival in MM, they appear to have limited activity against CNS MM and, paradoxically, may contribute to the evolution of resistant MM clones capable of surviving within the CNS. We undertook a retrospective analysis to characterize the features of CNS MM and outcome in 17 patients from four institutions identified between 2000 and 2011. The median age was 58 years. Patients had received a median of three prior therapies and all had been exposed to at least one of the so‐called novel anti‐MM agents before the diagnosis of CNS MM. The median time to CNS disease from initial diagnosis was 36 months. Cerebrospinal fluid (CSF) light chain measurements produced discrepant results to serum light chain measurements in some patients. Treatments included systemic pharmacotherapy, intrathecal (IT) chemotherapy and/or radiotherapy (RT). The median overall survival (OS) from diagnosis of CNS MM was only 4 months. OS was significantly better in patients who received IT chemotherapy (20 months vs. 2 months, respectively; P  < 0·02). We conclude that the systematic evaluation of IT therapy and diagnostic utility of CSF light chain measurements in CNS MM are warranted.